Being Malaysia - Sim, Steven 1982- (Penang Institute, 2018)
An impressive, insightful effort. In it, Steven writes about his reflections over the years as an MP on the issues of ideology b, religion, race relations, identity politics, the economy and good governance. He shares his thoughts freely, even encouraging us to imagine the possibilities democracy will offer us if we only go out and demand it from our political representatives and our government.